M64. ADDRESSING THE ROLE OF TIMING ON COGNITION IN SCHIZOPHRENIA. (18th May 2020) - Alústiza, Irene; Sol Garcés, María; Goena, Javier; Albajes-Eizagirre, Anton; Ortuño, Felipe
Abstract: Background: Schizophrenia (SZ) patients show activity deficits in brain regions that are conventionally associated with time perception. The dysfunction observed during timing tasks partially coincides with that evidenced during change-detection ones (both of attentional processing during odball paradigm and of preattentional processing in the mismatch negativity response). The implication is that timing dysfunction might underlie aberrant Salience Network (SN) and therefore cognitive impairment observed in SZ. In order to support this idea, we would like to examine it in HC. We hypothesize that neuroanatomical bases of time and salience processing are highly shared and interrelated not only in SZ but also in HC. The principal objective of this study was to elucidate whether there are any brain regions that show overlapped response during timing and oddball tasks in HC. Methods: We conducted three independent comprehensive literature searches of whole-brain functional magnetic resonance imaging (fMRI) studies in HC using timing and oddball tasks. The searches were applied to the PubMed search engine up to October 2019. Keywords used in the first search were: (("Temporal processing" OR "temporal discrimination" OR "time perception" OR "temporal estimation" OR "time estimation" OR "internal clock" OR "interval timing" OR "timing") AND ("functional magnetic resonance imaging" OR "fMRI") AND ("healthy volunteers" OR "healthy comparison" OR "healthy adult participants" OR "healthy comparison subjects" OR "healthy control subjects" OR "healthy subjects" OR "healthy individuals" OR "healthy participants" OR "healthy controls" OR "healthy" OR "controls" OR "control subjects")). Keywords used in the second search were: (("oddball") AND ("event-related")) together with the terms mentioned above referring to HC and fMRI. Last search used the same keywords but combined with ("mismatch negativity" OR "MMN"). We excluded studies that 1) used a region-of-interest approach; 2) did not report peak coordinates; 3) used different statistical thresholds in different regions of the brain; 4) used techniques other than fMRI; 5) were case reports, qualitative studies, reviews or meta-analyses. We ran three signed differential mapping (SDM) meta-analyses of fMRI studies assessing the brain response to timing and oddball paradigm in HC. Then, we carried out a multimodal meta-analysis to combine the findings from the three previous SDM meta-analyses. Results: Our initial search returned several papers, but application of inclusion criteria reduced this number to 17. Among them, 8 studied timing (which included a total of 129 HC), 8 examined attentional oddball paradigm (which included a total of 125 HC) and 3 MMN (which included a total of 52 HC). Meta -analysis results of timing studies HC showed significantly activation in left supplementary motor area (BA 8), left middle frontal gyrus (BA 10), right inferior frontal gyrus (BA 45), right supramarginal gyrus (BA 40), corpus callosum, left inferior network, left striatum, right superior longitudinal fasciculus and left cerebellum. Meta-analysis results of attentional oddball paradigm studies HC showed significantly activation in right supplementary motor area (BA 32), left postcentral gyrus (BA2), right rolandic operculum (BA 48), right supramarginal gyrus (BA 40) and left insula (BA 48). Meta-analysis results of preattentional oddball paradigm studies HC showed significantly activation in corpus callosum. Discussion: The current study supports the hypothesis that there exists an overlap between neural structures engaged by both timing and oddball tasks in HC. Since timing might be a primary cognitive function, its better understanding could help to improve the approach of treatment in SZ.